Pretreatment of aluminium: topography, surface chemistry and adhesive bond durability - Digby, R.P.; Paekham, D.E.
This paper reports on work in which bonded joints between a clad aluminium alloy (L165, comprising Cu 4.4
Keywords: ADHESIVE-BONDED JOINTS; ALUMINIUM; PRETREATMCNT; SURFACE TOPOGRAPHY; SURFACE CHEMISTRY; DURABILITY